1998
DOI: 10.1180/000985598545561
|View full text |Cite
|
Sign up to set email alerts
|

Influence of montmorillonite on Fe(II) oxidation products

Abstract: Goethite and maghemite are the stable species of Fe oxyhydroxides-oxides formed an acidic and alkaline environments from the oxidation of Fe(II) perchlorate solutions. The influence of montmorillonite on the oxidation products of 0.02 M ferrous perchlorate at pHs of 6.0 and 8.0 was studied by X-ray diffraction, infrared and transmission electron microscopic analyses. Increased rate of OH consumption during the oxidation at constant pH indicated that the presence of montmorillonite accelerated the rate of Fe(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Figure A shows that the redox potentials rapidly decreased with addition of aqueous Fe(II) to MONT suspensions and reached the experimental potential values of the Fe(II)/hydrous ferric oxide [HFO(s)] couple at pH 6.0 and that of the Fe(II)/lepidocrocite [γ-FeOOH(s)] couple at pH 7.5 . These observations are in good agreement with those of Krishnamurti et al who reported the influence of montmorillonite surface on ferrihydrite (HFO) and lepidocrocite (γ-FeOOH) formation at pH 6.0 and 8.0, respectively. Therefore, the measured redox potentials are in favor of the formation of hydrous ferric oxide (HFO) at pH 6.2 and lepidocrocite (γ-FeOOH) at pH 7.5 as possible oxidation products of Fe(II) sorbed on strong sites of MONT.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Figure A shows that the redox potentials rapidly decreased with addition of aqueous Fe(II) to MONT suspensions and reached the experimental potential values of the Fe(II)/hydrous ferric oxide [HFO(s)] couple at pH 6.0 and that of the Fe(II)/lepidocrocite [γ-FeOOH(s)] couple at pH 7.5 . These observations are in good agreement with those of Krishnamurti et al who reported the influence of montmorillonite surface on ferrihydrite (HFO) and lepidocrocite (γ-FeOOH) formation at pH 6.0 and 8.0, respectively. Therefore, the measured redox potentials are in favor of the formation of hydrous ferric oxide (HFO) at pH 6.2 and lepidocrocite (γ-FeOOH) at pH 7.5 as possible oxidation products of Fe(II) sorbed on strong sites of MONT.…”
Section: Resultssupporting
confidence: 89%
“…Unlike Fe(II), the sorption of U(VI) does not increase as much as Fe(II) with increasing pH. The increased uranium sorption is linked to the increase of Fe(II) sorption and the subsequent formation of a Fe(III) oxy-hydroxide surface coating as a result of surface oxidation of Fe(II) on MONT (33). Fe(II) and U(VI) show a small increase of sorption within the first hour of reaction, then remain constant within the investigated period of 72 h.…”
Section: Resultsmentioning
confidence: 92%
“…the exact formula of the TCA product would be (Zn0. Fe at 365-shoulder, 412, 465-shoulder, 602, 670-shoulder, deformation fluctuations Fe-O...Fe at 798, 906 cm -1) and of 0,-FeOOH (360, 472, 590-shoulder, 746, 1022 cm -1) are close to those described in the literature for phase-pure hydroxides [15]. The spectra of TCA samples reflect parallel processes of decomposition of the stock substances and synthesis of zinc ferrite with defective inverse structure.…”
Section: Resultssupporting
confidence: 67%
“…3. The reaction scheme is based on the method reported by Krishnamurti et al [28]. In the reported work, magnetite crystals were easily precipitated on a montmorillonite surface by adding montmorillonite to an alkaline solution of Fe 2+ .…”
Section: Preparation Of M-lmomentioning
confidence: 99%
“…The oxidation of Fe 2+ ions results in precipitation of Fe(OH) 3 on the LMO surface, and Fe 3 O 4 (magnetite) is formed by coprecipitation of Fe(OH) 3 with Fe(OH) 2 in the mixture [28]:…”
Section: Preparation Of M-lmomentioning
confidence: 99%